(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda science has been explained in the form of Hetu, Linga and Aushadha, where Aushadha has been given the much importance as success of treatment depends upon the usage of medicine considering the dose, time as well as the forms of medicine. Various sources are available to be used in the form of medicines as Herbs, Metals/Minerals or Animal products. Processed Metals/ Minerals such as Copper, Lead, Mercury were used in Ancient times but as the time goes, there was a drop in the usage of Herbomineral preparations in practice considering the claims put on its safety. Bruhatrayee being the most ancient and authentic texts of Ayurveda provides ample of references regarding usage of Herbomineral preparations for treatment of various conditions.